Justice: Social-psychological aspects - Suslavičius, Antanas (Psichologija, 1993)
The article discusses social-psychological aspects of justice. Theories of learning (G. Homans) and social exchange are presented. The distributive justice and its rules are analyzed. The peculiarities of the feeling of injustice are reviewed.